(untitled) (Global Journal of Management and Business Research, 2014)
The aim of this paper is to analyze the processes of adaptation and survival of companies in Mexico to compete in increasingly demanding markets, that create uncertainty them. In this context, some companies have decided to develop adaptation strategies through research and development (R & D). This study, being exploratory, provides empirical evidence on what factors (internal and external) leading the entrepreneurs to assess the implementation of R & D in their companies.